MARKETING STRATEGY IN IMPROVEMENT SELLING VALUE OF OYSTER MUSHROOM CULTIVATION - Siahaan, Rumiris; Winda Hardiyanti Damanik, Sri; Etri Jayanti.S, Suci; Purba, Rakhmawati; Piter Sony Hutauruk, Rapat; Zurlaini, Ayu (RADJA PUBLIKA, 2022)
This study explains how the Marketing Strategy in Increasing the Selling Value of Oyster Mushroom Cultivation. In this community service, it is focused on oyster mushroom cultivators, in Blok Village. 10, Dolok Masihul District, Serdang Bedagai Regency. This community service is carried out in Blok Village. 10, Dolok Masihul Subdistrict, Serdang Bedagai Regency, because this village has high potential in oyster mushroom cultivation. Cultivated edible mushrooms such as: straw mushrooms, oyster mushrooms, ear mushrooms and dark chocolate mushrooms.